Inovasi Pembelajaran Kurikulum Merdeka di Era Society 5.0 - Wannesia, Bunga; Rahmawati, Fanni; Azzahroh, Faridatun; Ramadan, Figo Muhammad; Agustin, Monica Elma (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
The background of the problem is that there are demands in Era Society 5.0, which must be able to solve various problems and social dynamics by utilizing technology. In various sectors and fields, challenges like this often arise, including in the field of education. This is what has led to several changes to the curriculum in Indonesia. Many other countries also always innovate curricula that have previously been made. At first, every curriculum that was made was considered ideal, but there would still be deficiencies so that changes, replacements or improvements were needed. In addition, human resources that are able to compete and adapt well are the main demands for a comprehensive change in all aspects. Therefore, the Free Learning Curriculum is here as an answer. The concept of the Free Learning Curriculum is also part of Society 5.0, where there is a combination of technology that continues to develop with various societal problems. This is proven, with the existence of technology that has become part of the social needs of every individual's life.